Financial depth, debt, and growth - Pasi Ikonen (Bank of Finland, 2017)
This thesis applies several econometric methods to a selection of country panels to study how growth is influenced by financial development and government debt. The first part presents the thesis discussion, including a synthesis on financial development, government debt, money supply, and economic growth. The second part deepens the discussion with three stand-alone essays. The first essay models how financial development affects growth through utilization of technological innovation. Based on explicit modeling of the innovation channel of finance, the results show a significant and positive sign for the interaction term between the measure of a country's own innovation and financial development in the most important specifications. This suggests that the innovation channel of finance is likely to be positively relevant to growth. The second essay examines effects of venture capital investment on economic growth in a similar framework. The findings demonstrate that the interaction of venture capital with innovation has a positive and statistically significant coefficient. Further, the joint impact related to venture capital and its interactions is positive in most specifications, suggesting that venture capital is probably a relevant factor for growth. The third essay delves deeply in the effects of general government debt and general government external debt on growth of real GDP. It explores the long-standing endogeneity problem, includes other relevant debt concepts besides government total debt, revisits the issue whether there are threshold values for the government debt ratio, examines the effect of debt on GDP components and structure, uses timely and extensive datasets and extensive robustness analysis, and runs meta-regressions of the results of this and a many of other studies. Even with correction for endogeneity, the study finds modest evidence of a negative and significant growth impact for government debt. The evidence is not robust over all samples and specifications. The final essay also reports evidence of a negative and significant effect of government external debt in the sample of developed economies. The findings overall comport with those of recent papers that conclude that there is no universal threshold value for a government debt ratio that would hold across all countries. Further, government debt appears to decrease the private-investment-to-GDP ratio, but increases the GDP ratio for household consumption. The meta-regression analysis shows that the study's results on how specification features affect the estimate of the government debt coefficient are broadly in line with those of other studies.
URN:NBN:fi:bof-201705171300
Keywords: 330; Wirtschaftswachstum; Endogenes Wachstumsmodell; Risikokapital; Finanzmarkt; Technischer Fortschritt; Innovation; Öffentliche Schulden; Ökonometrisches Modell